Invasive meningococcal infections in children during the 1998–2001 hyper-endemic period in Switzerland - Zimmerli, Joerg; Aebi, Christoph (Journal of Pediatric Infectious Diseases, 2006)
Pediatric cases of invasive meningococcal disease (IMD) during the 1998 to 2001, hyperendemic period in Switzerland, were investigated. Retrospective analysis of confirmed and probable cases of IMD, in patients <16 years of age, identified at the University of Bern Children's Hospital, during a 5-year period beginning on February 1, 1997, was done. Sixty-two cases were identified (22% of nationally reported cases of pediatric IMD). Thirty-eight cases (61%) were culture confirmed. Probable cases were clinically indistinguishable, but significantly more likely to be secondary referrals and to have received pre-admission antibiotics (OR 5.4; 95%CI 1.8–16.4). The proportion of confirmed cases was significantly smaller than among all cases reported to the Swiss Federal Office of Public Health (83%; OR 0.32, 95%CI 0.19–0.57). The distance between the patients' place of residence and the tertiary care center did not correlate with the delay from onset of IMD to treatment and admission. The presence of petechiae (n = 38) was associated with a significantly shorter median delay from onset of IMD to admission (18 vs. 25 hours, P = 0.016). Case fatality rate was 5%. In conclusion, secondary referrals of IMD patients, having received pre-admission antibiotics, reduce the number of culture-confirmed cases. The large proportion of culture-negative (i.e., probable) IMD cases in comparison with national data indicates that probable cases are incompletely reported to the federal authorities. Additional efforts (e.g., meningococcal polymerase chain reaction) are needed to improve the surveillance of pediatric IMD in Switzerland.
Keywords: Neisseria meningitides; serogroup C; child; epidemiology; meningococcal conjugate vaccine